Gender Differences in the Interpretation of Experiences of Patients with Tuberculosis in Medellín, Colombia - Liliana Villa Vélez; María Patricia Arbeláez Montoya (Universidad de Antioquia, 2015)
Objective. This study sought to determine gender differences in the interpretation of tuberculosis (TB) in a group of patients from the city of Medellín. Methodology. This was a qualitative study, with the grounded theory method. Twelve semistructured interviews were applied to patients from both genders who were cured of TB. The sample was selected through convenience and for analysis the information was categorized through the Atlas Ti tool. Results. Regarding the symptoms, the most reported is cough, but men manifest expectoration more frequently. Men overstated the symptoms, while women tend to minimize them. Women report mental impairment and emotional-type manifestations produced by the disease. Men and women expressed ignorance about the disease upon diagnosis. Both manifested fear of infection, work incapacity, loss of employment, rejection by others, and death. Also highlighted is the importance of family support and of the healthcare personnel. Women expressed shame in that others knew of their disease and mentioned greater intolerance with taking the medications. Conclusion. The gender role constructed culturally constitutes the central axis that explains how men and women interpret TB and can be modified by educational and accompaniment processes. Family support plays an important role in the healing process. Although common aspects exist, delving into the gender differences against the interpretation of TB may permit a different approach of the disease and better control of it.